If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 8 = -122 + -9x Reorder the terms: 8 + 6x = -122 + -9x Solving 8 + 6x = -122 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 8 + 6x + 9x = -122 + -9x + 9x Combine like terms: 6x + 9x = 15x 8 + 15x = -122 + -9x + 9x Combine like terms: -9x + 9x = 0 8 + 15x = -122 + 0 8 + 15x = -122 Add '-8' to each side of the equation. 8 + -8 + 15x = -122 + -8 Combine like terms: 8 + -8 = 0 0 + 15x = -122 + -8 15x = -122 + -8 Combine like terms: -122 + -8 = -130 15x = -130 Divide each side by '15'. x = -8.666666667 Simplifying x = -8.666666667
| 183-2x=43x+23 | | 9-10x=209-45x | | 2x+3(x-5)=5(2x-3) | | 2mn+9mp= | | 4(x+3)-7x=6 | | 10-3x+8=30+2x+48 | | 17x+8=42 | | 9x-6-5x=8+x-14 | | 56-6x=3x+21 | | 5-7x=3x+21 | | -70-9x=43-21x | | (5y-2)=52 | | 14-8x+6-5x=10+2x-5 | | 6x+18=116-6x | | (x+2)(2-x)=6x-x | | 2x+36=21x-36 | | 17-6x=4x-8 | | 9-5k+2k=k-23 | | x^2+4x-1=9x-5 | | 6x+30=13-33 | | x^2+8x-2=7 | | x^2-(a+2b)x+b^2+ab=0 | | 24a=36 | | 12-x=30-4x | | 3x+4=5x-16 | | x^2+32x-196=0 | | x-17=6x+8 | | 9x-5=x+19 | | 9x+6=6x+10 | | 7x-20=04-3x | | 7(2x-5)=42 | | 21-7x=10+4x |